Ananthanarayan and Paniker's Textbook of Microbiology - R Ananthanarayan (University Press, 2005)
In this new edition, the classic textbook has been relevant new information and all chapters have been thoroughly revised and updated. It contains current material on HIV, hepatitis virus, SARS, coronavirus, bird flud virus and many of the new agents responsible for human infections. The epidemological patterns have been redescribed and updated. This New Edition, The classic textbook has been relevant new information and all chapters have been thoroughly revised and updated. It contains current material on Hiv, Hepatitis Virus, Sars, Coronavirus, Bird Flud Virus and many of the new agents responsible for human infections. The epidemological patterns have been redescribed and updated.